The relationship between umbilical artery Doppler findings, fetal biophysical score and placental inflammation in cases of premature rupture of membranes - Yucel, N; Yucel, O; Yekeler, H (Munksgaard Int Publ Ltd, 1997)
Background. To assess the relationship between placental inflammation, umbilical artery Doppler waveforms and fetal biophysical profile score, umbilical artery Doppler studies and fetal biophysical evaluations were performed in 24 preterm pregnants with premature rupture of membranes (PROM). Subjects. After delivery, the placentas were microscopically examined and two subgroups were formed including noninflamed or inflamed placentas. Results. In the first group, which includes 14 cases with no histological signs of placental inflammation, we found increased systolic/diastolic ratio only in ope patient, whereas in the second group including ten cases with microscopically proven inflammation, nine were found to have increased systolic/diastolic ratios (p<0.05). Mean systolic/diastolic ratio in the first and the second groups were 2.74+/-0.18 and 4.64+/-0.93 respectively (p<0.001). Mean biophysical profile score was 9+/-1.04 in the first group and 7+/-1.05 in the second group (p<0.001). Conclusion. Abnormal biophysical profile scores along with increased arterial systolic/diastolic ratios have been shown to be the markers of impending clinical infection.
Keywords: color Doppler ultrasonography; fetal biophysical profile score; placental inflammation; premature rupture of membranes; umbilical artery